Death and the mother from Dickens to Freud : Victorian fiction and the anxiety of origins - Dever, Carolyn (Cambridge studies in nineteenth-century literature and culture, 1998)
The cultural ideal of motherhood in Victorian Britain seems to be undermined by Victorian novels, which almost always represent mothers as incapacitated, abandoning or dead. Carolyn Dever argues that the phenomenon of the dead or missing mother in Victorian narrative is central to the construction of the good mother as a cultural ideal. Maternal loss is the prerequisite for Victorian representations of domestic life, a fact which has especially complex implications for women. When Freud constructs psychoanalytical models of family, gender and desire, he too assumes that domesticity begins with the death of the mother. Analysing texts by Dickens, Collins, Eliot, Darwin and Woolf, as well as Freud, Klein and Winnicott, Dever argues that fictional and theoretical narratives alike use maternal absence to articulate concerns about gender and representation. Psychoanalysis has long been used to analyse Victorian fiction; Dever contends that Victorian fiction has much to teach us about psychoanalysis.